Forrobodó: uma expressão literária afro-brasileira - Moura, Hernany Donato de (2024)
The present work develops the thesis that forró, according to its trajectory in the 20th century, represents a set of representative literary expressions of the Afro-Brazilian population. A musical genre composed of several cultural elements inserted in their respective diasporas in the Northeast/Southeast of Brazil, it concentrated an expressive popular diversity in the dance of the race present in the concept of forrobodó. By race dance we mean the set of racial attitudes that represented the Brazilian black in the construction of their symbolic identities based on actions of associativism and resistance in the formation of Brazil in the last century, based on literary and musical genres of oral culture in an environment urban. The problematization of the present study is based on the assumption that several expressions of Brazilian culture were chosen as national representations of popular culture by intellectuals and/or by policies to encourage Brazilian culture. Respectively, the literature produced in the first decades of the twentieth century in the Brazilian modernist movement and the samba that had fruition in the city of Rio de Janeiro. Although, they were not enough to establish a connection, even if symbolic, of national identity, therefore, it is up to us to question why forró, which is also a manifestation of popular culture and present in the cultural formation of Brazilian society from the 19th century to the present , is not recognized as an element of a Brazilian identity? To answer this question and develop the thesis, it was essential to retrace the path of the collections, especially digital ones, mainly through newspaper journals and radio magazines available in the Hemeroteca Digital Brasileira and also in specialized sites in the broad genre of forró, in order to explore and study in the work of two great icons of this musical genre, Luiz Gonzaga (1913-1989) and Jackson do Pandeiro (1919-1981), the way in which forró can be defended as an Afro-Brazilian literary expression. For this, we compare the data collected with the theoretical contribution of black men and women intellectuals, whether from the black diaspora around the world, or intellectuals of Brazilian social thought, always reflecting on the autonomy of popular culture as a building element of the idea of nation in the context of the years 1940 to 1980. According to what was analyzed in the course of this research, we could see that forró is constituted as a literary expression, which brings in its genesis influences and peculiarities representative of Afro-Brazilian culture at the national level, however it is not widely recognized, because such references concern the northeastern black, who populated Brazil, especially in the spaces of construction of black urbanity and modernity. This freewheeling Afro-Brazilian literary expression brought with it the racial experience based on ancestry and joined the experiences of black people from the Northeast acquired in modernity and in its diaspora in the national territory. In this sense, forró gave rhythm to Brazilian modernity, mainly in the Southeast.